Use of Jerango (Acorus calamus) for Various Diseases Treatment in Eight Ethnics in Aceh Province - Rahma Widyastuti; Galuh Ratnawati; Saryanto Saryanto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Medicinal plants in Indonesia, many varieties in use in various regions, according to the local wisdom of each ethnic group. Jerango (Acorus calamus) is one of medicinal plants used for treatment. At RISTOJA in Aceh Province, Jerango is used by hattra for treatment. The aim of the study was to identify and describe the use of jerango for treatment by various ethnic groups in Aceh Province. The data used were data from RISTOJA research results from the Laboratory of Health Research and Development Agency Data Management. The variables analyzed were various types of diseases that could be treated using jerango potions and the ingredients parts of jerango used by hattra in 8 ethnic groups in Aceh province. The result is that there are 29 jerango herbs used for the treatment like cough, fever / heat, vitality disorders, HIV / AIDS, poisoning, ulcers, magic, diarrhea, childhood illness, venereal disease, pre / postpartum care, headaches, tumors / cancer, and hemorrhoids. Jerango is most widely used for the treatment of pre / postpartum care, cancer / tumors and childhood diseases and for the purposes of things related to magic. While the most widely used part of the jerango plant for treatment is the rhizome. Keywords: A. calamus, Aceh, Ristoja, ethnic